The validation of the organizational change construct using confirmatory factor analysis - Naveed, Rana Tahir; Jantan, Amer Hamzah; Saidu, Mohammed Bashir; Bhatti, Saad Mahmood (Cogent OA, 2017)
Organizational changes play a vital role in development of organizations. Development can only be possible through change. Numerous researches have been conducted to explore organizational change aspect descriptively but no attempt has been made to validate and develop instrument to measure behaviours and thoughts of employees regarding organizational change. This study identified and used nine dimensions to measure organizational change, and 380 Bank managers were surveyed using a self-administered questionnaire. To conform the dimensions and their contributions towards main construct, first-order and second-order confirmatory factor analysis has been conducted using SEM—AMOS. The result showed that process, strategy, attitude, structure, culture and technology are the main predictors of organizational change.